(untitled) (Journal of Pedagogical Inventions and Practices, 2023)
Internal combustion engines (ICEs) have long been the backbone of automotive and mechanical industries, propelling our society forward through efficient power generation. This scientific article explores the multidimensional aspects of ICEs, encompassing their historical development, operational principles, environmental impacts, and contemporary advancements. The article provides a comprehensive overview of the paradigm shifts and promising technologies that continue to enhance the performance, efficiency, and sustainability of internal combustion engines.